The Implementation of Role-Playing Activities to Enhance the Language Skills of Children Aged 5–6 Years - Ahmad Maududi (Journal of Education, Teaching, and Learning, 2025)
This study aims to improve the language skills of children aged 5–6 years at TK IT Permata Hati during the 2024/2025 academic year. The research was conducted using a Classroom Action Research (CAR) design, which comprised two cycles, namely Cycle I and Cycle II. Each cycle involved four stages: planning, implementation, observation, and reflection, allowing for continuous assessment and refinement of teaching strategies. The study focused on 18 children in Group B at TK IT Permata Hati, Wanasaba District, consisting of 4 boys and 14 girls. Data were collected through direct observation, performance assessment, and documentation, providing a comprehensive view of the children’s language development. The findings revealed significant improvement in children’s language skills following the implementation of the role-playing method. In Cycle I, the achievement percentage based on observation sheets was 72.2%, which increased to 78% in Cycle II, reflecting a 5.8% improvement. Similarly, the class average score increased from 62.4 in Cycle I to 73.15 in Cycle II. These results indicate that the role-playing method effectively fosters language development in young learners by providing an engaging, interactive, and contextually meaningful learning environment. Children were observed to participate more actively, communicate with greater confidence, and demonstrate an increased ability to construct sentences and express ideas. Overall, the study highlights that integrating role-playing activities into early childhood education can significantly enhance language skills, supporting both cognitive and social development. The positive outcomes suggest that such methods can be applied more broadly in similar educational settings to optimize language learning for preschool-aged children.